Complete Chloroplast Genome Sequence of Erigeron breviscapus and Characterization of Chloroplast Regulatory Elements - Yu, Yifan; Ouyang, Zhen; Guo, Juan; Zeng, Wen; Zhao, Yujun; Huang, Luqi (Frontiers in Plant Science, 2021)
Erigeron breviscapus is a famous medicinal plant. However, the limited chloroplast genome information of E. breviscapus, especially for the chloroplast DNA sequence resources, has hindered the study of E. breviscapus chloroplast genome transformation. Here, the complete chloroplast (cp) genome of E. breviscapus is reported. This genome was 152,164 bp in length, included 37.2 % GC content and was structurally arranged into two 24699 bp inverted repeats and two single-copy areas. The sizes of the large single-copy region and the small single-copy region were 84,657 bp and 18,109 bp, respectively. The E. breviscapus cp genome consisted of 129 coding genes, including 83 protein coding genes, 36 transfer RNA (tRNA) genes, and 8 ribosomal RNA (rRNA) genes. For those genes, 95 genes were single copy genes and 16 genes were duplicated in two inverted regions with seven tRNAs, four rRNAs, and five protein coding genes. Then, genomic DNA of E. breviscapus was used as a template, and the endogenous 5’ and 3’ flanking sequences of the trnI gene and trnA gene were selected as homologous recombinant fragments in vector construction and cloned through PCR. The endogenous 5’ flanking sequences of the psbA gene and rrn16S gene, the endogenous 3’ flanking sequences of the psbA gene, rbcL gene and rps16 gene and one sequence element from the psbN-psbH chloroplast operon were cloned, and certain chloroplast regulatory elements were identified. Two homologous recombination fragments and all of these elements were constructed into the cloning vector pBluescript SK (+) to yield a series of chloroplast expression vectors, pBluescript-EGFP, which harbored the reporter gene EGFP and the selectable marker aadA gene. After identification, the chloroplast expression vectors were transformed into E. coli and the function of predicted regulatory elements was confirmed by a spectinomycin resistance test and fluorescence intensity measurement. The results indicated that aadA gene and EGFP gene were efficiently expressed under the regulation of predicted regulatory elements and the chloroplast expression vector had been successfully constructed, thereby providing a solid foundation for establishing subsequent E. breviscapus chloroplast transformation system and genetic improvement of E. breviscapus.